Empowerment Pendidikan Agama Islam: Membendung Arus Radikalisme Agama di Perguruan Tinggi Umum - Ade Imelda Frimayanti; Mualimin Mualimin; Diana Diana (Journal on Education, 2024)
This research is motivated by the emergence of radical organizations that exploit religion and frequently target university students, especially those in public universities. The purpose of this study is to analyze the role of Islamic religious education courses at public universities in countering the tide of religious radicalism. This research employs the library research method to collect data and information relevant to the topic or research problem through an in-depth literature review. The results of this study indicate that empowerment in the context of Islamic religious education involves the development of learning materials, teaching models, and the enhancement of lecturer professionalism. Islamic religious education materials need to be composed from various perspectives or schools of thought to enhance students' understanding and tolerance of differences. Developing teaching models that instill anti-radicalism values such as tolerance, democracy, gentleness, and taawun (cooperation) is essential for fostering an inclusive attitude among students. The professionalism of Islamic religious education lecturers who have a moderate understanding is key in this empowerment process, enabling them to function as role models and mentors in instilling peaceful and inclusive Islamic values. Thus, Islamic religious education can become an effective tool in empowering students to recognize and reject radical ideologies and promote a moderate attitude in their religious practices.